Bibliometric review using ProKnow-c: supply chain: analysis in coffee distribution - Ribeiro, Ana Beatriz; Cosvock, Enzo Almenara; Cupertino, Gustavo; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2025)
This article presents a bibliometric review using the ProKnow-C methodology to analyze the supply chain in coffee distribution. The study aimed to identify research gaps and propose improvements in the coffee production chain, which is essential for its competitiveness in the global market. From an initial portfolio of 2,238 articles, eight relevant studies were selected after rigorous filtering stages, including duplicate elimination, title analysis, abstract review, and full-text reading. The results highlighted the relevance of themes such as agribusiness, supply chain, and inventory management, with an emphasis on the impact of tools like Lean Manufacturing, TPM (Total Productive Maintenance), and risk management. It was observed that logistical bottlenecks, inadequate infrastructure, and the need for modernization are challenges shared between coffee and other agricultural commodities. The study concludes that adopting innovative and technological practices is crucial to optimizing operational efficiency and strengthening the competitiveness of the coffee sector.